Sengketa Penguasaan Hak Atas Tanah: Refleksi Terhadap Sengketa Tanah Antara TNI dan Masyarakat - Layyin Mahfiana (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2007)
This study aims to analyze disputes over land rights between the Indonesian National Armed Forces (TNI) and the community and their implications for land policy in Indonesia. This study explores the factors causing disputes, the legal basis used by each party, and potential solutions that can be applied. The methods used were library research and case analysis with a descriptive-qualitative approach. Data was obtained from legal documents, laws and regulations, and court decisions related to land dispute cases. The results showed that land disputes between the TNI and the community are generally caused by overlapping land rights claims, land administration discrepancies, and historical land ownership factors. Dispute resolution often faces legal and social obstacles, requiring more transparent and equitable policies. This study recommends strengthening the land administration system and a mediation approach to resolve conflicts in a sustainable manner.